Profile of Students’ Critical Thinking Skills in the Sub-Concept of Environmentally Friendly Technology in the Energy Sector - Evi Heri Kustanti; Nur Khoiri; Joko Siswanto (Jurnal Penelitian Pembelajaran Fisika, 2026)
This research aims to determine the critical thinking skills of class IX students of SMP Negeri 2 Selopampang, Temanggung Regency on the sub-concept of environmentally friendly technology in the energy sector. Sampling for this research used a convenience sampling technique where the sample was chosen freely according to the wishes of the researcher. The research subjects were 24 students in class IX C of SMP Negeri 2 Selopampang for the 2022/2023 academic year. The instrument used in the form of a written test refers to the critical thinking indicators developed by Ennis. The indicators of critical thinking skills measured are: 1) providing a simple explanation (elementary clarification); 2) build basic skills (basic support); 3) drawing conclusions (inference); and 4) provide further explanation (advanced clarification); and 5) organize strategies and tactics (strategies and tactics). The results of the research show that the overall profile of students' critical thinking skills in the environmentally friendly technology sub-concept in the energy sector is in the low category. The implications of this research can provide information about critical thinking skills.